Porous nonhierarchical CeO2-SiO2 nanocomposites for improving the ultraviolet resistance capacity of polyurethane coatings - Bac Quang Nguyen; Chuc Ngoc Pham; Chi Thi Ha Nguyen; Dung Trung Doan; Lim Thi Duong; Nghia Pham Ngo; Mai Vu Ngoc Nguyen; Hoang Van Cao; Lam Dai Tran and Ngoc Nhiem Dao (My University, 2021)
Porous nonhierarchical CeO2-SiO2 nanocomposites for improving the ultraviolet resistance capacity of polyurethane coatings
Keywords: CeO2-SiO2